EFFECTS OF FOLIAR APPLICATION OF ORGANIC AND GROWTH PROMOTER BIOZYME ON GROWTH OF WOLLY PEACH "RED JUNE" 2- leaves nutrients concentrations - & Al-Biaty, Al-Karam (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
A Factorial experiment within Randomized Complete Block Design was coducted during 2014, 2015 on wolly peach seedlings C.V Red June, which grafted on the seeded apricot , at the Dept. of Horticulture – Coll. Of Agric. – Univ. of Baghdad. The objective of this experiment was to study the effect of foliar application The seedlings were sprayed with four levels of organic fertilizer Botryfun is 0, 3, 4 and 5( Ml.ltr-1) for each level by the symbol F0, F1, F2 and F3 respectively, growth prpmoter Biozyme three levels are 0, 2 and 4(Ml.ltr-1) are indicated G which is G0, G1 and G2 respectively, recorded most of the treatment were significant differences for the control, were the highest values of organic fertilizer in the treatment of F3 to all the elements reaching nitrogen 1.10 and 1.57 %, phosphorus 0.37 and 0.64%, potassium 2.16 and 2.66 %, iron 244.89 and 245.11 ppm, manganese 64.60 and 73.67 ppm, and zinc 105.33 and 128.67 ppm for two seasons respectively. And gave a growth promoter at the third focus G2 highest rates in the stock content from the elements, as it gave the nitrogen 1.10 and 1.54%, phosphorus 0.37 and 0.49%, potassium 2.01 and 2.57%, manganese 61.33 and 72.67 ppm,  and zinc 100.00 and 127.67 ppm, except iron of both seasons. When overlap outperformed many treatment morally for the control were treated overlap G2F3 with the highest value for all nutrients studied, which amounted to 1.12 and 1.70% nitrogen, 0.43 and 0.50.% Phosphorus, 2.22 and 2.78% potassium, 241.67 and 242.00 ppm iron , 68.00 and 86.67 ppm, manganese 121.67 and 132.00 ppm zinc. while the control recorded lower values and all the nutrients studied.